A combined bottom-up and top-down strategy to fabricate lanthanide hydrate@2D MOF composite nanosheets for direct white light emission. Issue 41 (12th October 2021) - Tang, Jianping; Liang, Zhenxin; Huang, Mengyi; Su, Shaodong; Wen, Yuehong; Zhu, Qi-Long; Wu, Xintao
Abstract : This study provides an efficient approach for fabricating white light emitting guest@2D MOF composite nanosheets via integrating bottom-up synthesis and top-down exfoliation. Abstract : Metal–organic frameworks (MOFs) have been demonstrated as excellent host matrices to encapsulate diverse guest molecules for fabricating functional composite materials. Many synthetic methods have been explored to prepare white light emitting (WLE) MOF composites; however, yielding easily solution-processable WLE guest@MOF nanocomposites remains a great challenge. In this work, we develop a novel strategy, i.e., in situ guest-introduction combined with the instant in situ exfoliation method, to fabricate WLE MOF composite nanosheets, which integrates the advantages of bottom-up synthesis and top-down exfoliation. By employing this strategy, the WLE lanthanide hydrate@2D MOF composite nanosheets with large average lateral dimensions of ∼1.2 μm × 500 nm and a thickness of ∼11.4 nm are rapidly constructed from 2D MOF precursors and lanthanide hydrate species in high yields. The white light can be finely tuned by adjusting the content of the included guest molecules, and the color-rendering index (CRI) reaches up to 92. This novel synthetic strategy has many advantages including high efficiency, facile and green synthesis, etc. The combined bottom-up and top-down strategy paves a new route to design and prepare functional guest@2D MOF composite nanosheets.